Pengembangan Aplikasi Mobile Geotagging Pembagian Zakat Fitrah Pada Platform Android - Rio Trilaksono Putro; Herman Tolle; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Zakat is one of the five pillars of Islam and is included in the section of faith that is often mentioned in the Qur'an. Zakat is a worship as well as prayer and shaum (fasting), and refusal to pay for it or dodge it from deliberate elements is the same as denying faith and Islam. Zakat is usually distributed by the mosques and charity bodies of zakat that is around us, as well as around the dwelling of the people who are entitled to receive it. However, the process of data collection and distribution of zakat is sometimes constrained by the location mustahik. Zakat committee is often difficult in making data collection and distribution of zakat fitrah to the house of people who are entitled to receive zakat fitrah. The committee is also difficult to find a house from mustahik. With the geotagging feature on the smartphone, we can use it as a means to perform data collection and distribution of zakat. By using geotagging, we can add geographical identity to various media such as photos. Based on the results of the validation testing shows that the system meets all requirements of functionality requirements and 100% valid. Whereas based on usability testing result, the test result reaches 80.34% mean that this system can be accepted and used well by zakat committee.